KNOWLEDGE MANAGEMENT STRATEGIES AS INTERMEDIARY VARIABLES BETWEEN ITBUSINESS STRATEGIC ALIGNMENT AND FIRM PERFORMANCE - Masa’deh, Ra’ed (Mohâ€™d Taisir); Obeidat, Bader Yousef; Al-Dmour, Rand Hani; Tarhini, Ali (European Scientific Journal, ESJ, 2015)
Since the relationship between knowledge management and ITbusiness strategic alignment should be investigated further, highlighting the importance of knowledge (both tacit and explicit) in the formation and implementation of IT strategy; this research aims to review and discuss the links between data, information, and knowledge; how researchers classify knowledge; the ways that firms could manage their knowledge and systems; the difficulties and challenges that firms might face when implementing knowledge management systems, and the ways in which managers should resolve such challenges; and empirical research on the linkage between knowledge management strategies and firm performance. Consequently, further research is needed to validate the ways researchers measure the associations among IT-business strategic alignment, knowledge management, and firm performance in both developed and developing countries and across different industries.